2017
DOI: 10.1097/sle.0000000000000366
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Anastomotic Leakage After Laparoscopic Low Anterior Resection in Male Rectal Cancer by Pelvic Measurement in Magnetic Resonance Imaging

Abstract: Objective:Anastomotic leakage after laparoscopic low anterior resection in male rectal cancer patients with a narrow pelvis cannot be easily resolved. The objective of this study is to assess numerical information of narrow pelvis and to determine whether prediction of morbidity can be possible.Methods:Retrospective medical record review was performed. From July 2007 to January 2013, 43 consecutive male patients with low rectal cancer who underwent laparoscopic low anterior resection were divided into the anas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…Similar to previous reports, the present study found a significant correlation between AS and AL, suggesting that AL and AS might have reciprocal consequences . This study also found that the male sex and narrow pelvis were independently associated with AL, in agreement with prospective, multi‐institutional studies showing that both were risk factors for AL . The lower sensitivity of APCT has been reported, whereas the clinical utility of WCE as a predictor of AL remains undetermined .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to previous reports, the present study found a significant correlation between AS and AL, suggesting that AL and AS might have reciprocal consequences . This study also found that the male sex and narrow pelvis were independently associated with AL, in agreement with prospective, multi‐institutional studies showing that both were risk factors for AL . The lower sensitivity of APCT has been reported, whereas the clinical utility of WCE as a predictor of AL remains undetermined .…”
Section: Discussionsupporting
confidence: 92%
“…3,8,13 This study also found that the male sex and narrow pelvis were independently associated with AL, in agreement with prospective, multi-institutional studies showing that both were risk factors for AL. 14,15 The lower sensitivity of APCT has been reported, 16 whereas the clinical utility of WCE as a predictor of AL remains undetermined. 17 We found several interpretative errors, including a pseudo diverticulum caused by a recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis provided results that were comparable to these previous findings. The pelvic index was also reported as a risk factor in a previous study [ 15 ]. Tsuruta et al reported that a smaller ratio of the mesorectum to the depth of the cavity of the lesser pelvis was associated with an increased risk of AL.…”
Section: Discussionmentioning
confidence: 98%
“…Previously reported risk factors for AL during surgery include the operation time, amount of intraoperative blood loss, and blood transfusion [ 13 , 14 ]. Tsuruta et al reported that a smaller ratio of the difference between the interspinous distance and diameter of the mesorectum to the depth of the lesser pelvic cavity (pelvic index) was associated with a higher risk of AL [ 15 ]. Similarly, a few studies have reported the detection of risk factors for AL using preoperative imaging findings [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pelvimeter is no longer just obstetric assessment tool, but widely used in the evaluation of rectal cancer before surgery. A lot of researches have proved that there is a link between the pelvic measurement parameters and operation time, intraoperative bleeding volume, difficulty of operation, ring margin positive rate, surgical specimen integrity, even postoperative anastomotic fistula of rectal cancer surgery [ 11 13 , 20 ]. In this study, two methods of laparoscopic surgery was used, one was laparoscopic anterior resection in which the part of the rectum containing the tumor was removed and the colon was then attached to the remaining part of the rectum so that bowels can be empty in the usual way, second was MILES which involved removal of the anus and the tissues surrounding it, including the sphincter muscle and a permanent colostomy was done since the anus was removed.…”
Section: Discussionmentioning
confidence: 99%